Beyond the days of the giants : navigating the succession crisis in public accounting - Fisher, Paul D. (Productivity Press, 2013)
During the next 10 years, an estimated 40-50 percent of the partners in public accounting firms will retire. This exodus will place an enormous intellectual and financial strain on firms as they scramble to train and promote new partners, retire the existing ones in an orderly manner, and find the profitability to do so in extraordinarily lean economic times. Beyond the Days of the Giants: Solving the Crisis of Growth and Succession in Today's CPA Firms is a practical, readable implementation guide for your firm to use during this next critical decade. It gives step-by-step guidance on how to: founded in practitioner-led value creation, Create a growth culture Build a no-new-cost practice system to operate within it , and Renew practitioner accountability, not to disappearing Giant-centered value creation systems, but to evidence-based value management practice --led by our New Giants.